Eleições 2018: monitoramento de notícias no Facebook - Palandi, Amanda Camillo (2019)
The traditional media has been competing with digital media more and more, and the one-all information mediation model has given way to the all-for-all format, in which consumer-citizens not only receive the information but interact with it and even produce it. Brands have benefited for at least two decades from monitoring these media using collection and analysis in data base tools, to stablish a connection with the audience, resolve crises, and especially achieve return on investment goals. In Brazil, digital social networks have become one of the main sources of news, and the study of interactions in these environments has great potential to understand behaviors and trends, including topics about politics. The 2018 elections brought a notorious political debate within these networks, and the president - elect used them for his campaign like never before. This study aims to analyze how news producers covered the electoral process in Facebook, and how Internet users reacted to the content aired